Functional dissection of the Hox protein Abdominal-B in Drosophila cell culture - Zhai, Zongzhao; Yang, Xingke; Lohmann, Ingrid (Biochemical and biophysical research communications, 2011)
Hox transcription factors regulate the morphogenesis along the anterior-posterior (A/P) body axis through the interaction with small cis-regulatory modules (CRMs) of their target gene, however so far very few Hox CRMs are known and have been analyzed in detail. In this study we have identified a new Hox CRM, ct340, which guides the expression of the cell type specification gene cut (ct) in the posterior spiracle under the direct control of the Hox protein Abdominal-B (Abd-B). Using the ct340 enhancer activity as readout, an efficient cloning system to generate VP16 activation domain fusion protein was developed to unambiguously test protein-DNA interaction in Drosophila cell culture. By functionally dissecting the Abd-B protein, new features of Abd-B dependent target gene regulation were detected. Due to its easy adaptability, this system can be generally used to map functional domains within sequence-specific transcriptional factors in Drosophila cell culture, and thus provide preliminary knowledge of the protein functional domain structure for further in vivo analysis.